Functional Endoscopic Sinus Surgery( FESS) - Nausheen Qureshi , Nighat Arif (Journal of Rawalpindi Medical College, 2017)
To study the management of the patients of various nasal and para nasal sinuses diseases with endoscopic sinus surgery in terms of age, gender, disease pattern, surgical procedures, complications and recurrence rate. Methods: In this descriptive study 146 patients of different sinonasal disease treated with endoscopic sinus surgery were included. Patients with CSF leak, nasolacrimal duct obstruction , polyps,with and without history of allergy and asthama were included. Patients with mucormycosis, invasive fungal sinusitis, malignancy and very elderly were not included. Pre-operative CT scan was a pre requisite in all patients. Fibreoptic light was passed through the canaliculi to identify the lacrimal sac or after dilating the puncta with a lacrimal probe,it was passed into the superior and inferior canaliculi to know the position of lacrimal sac .The lacrimal sac is located lateral to the maxillary line at its superior edge. Drill was used to create a window.All patients had their visual acuity , colour vision and funduscopy done prior to surgery. Flourescein dye was used for CSF rhinorhea demonstration prior to CSF leak repair preoperatively. On the 4th postoperative day the patients had removal of their crusts and had examination of nasal cavity. Results: Mean age was 33 years. The commonest presenting feature was nasal obstruction and nasal discharge. Most of the patients had allergic fungal sinusitis though we did manage to do isolated cases of sphenoiditis, a couple of DCR and of CSF Rhinnorhea. The most common complication we encountered was recurrence of disease followed by periorbital pain and bruising and pain. Conclusion: Endoscopic sinus surgery is the standard of care in modern rhinology and more work is required in our country to promote its training and use for the betterment of patients.